Patterns of Red and Processed Meat Consumption and Risk for Cardiometabolic and Cancer Outcomes A Systematic Review and Meta-analysis of Cohort Studies - Vernooij, Robin W. M.; Zeraatkar, Dena; Han, Mi Ah; El Dib, Regina [UNESP]; Zworth, Max; Milio, Kirolos; Sit, Daegan; Lee, Yung; Gomaa, Huda; Valli, Claudia; Swierz, Mateusz J.; Chang, Yaping; et al. (Amer Coll Physicians, 2019)
Background: Studying dietary patterns may provide insights into the potential effects of red and processed meat on health outcomes. Purpose: To evaluate the effect of dietary patterns, including different amounts of red or processed meat, on all-cause mortality, cardiometabolic outcomes, and cancer incidence and mortality. Data Sources: Systematic search of MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, CINAHL, Web of Science, and ProQuest Dissertations & Theses Global from inception to April 2019 with no restrictions on year or language. Study Selection: Teams of 2 reviewers independently screened search results and included prospective cohort studies with 1000 or more participants that reported on the association between dietary patterns and health outcomes. Data Extraction: Two reviewers independently extracted data, assessed risk of bias, and evaluated the certainty of evidence using GRADE (Grading of Recommendations Assessment, Development and Evaluation) criteria. Data Synthesis: Eligible studies that followed patients for 2 to 34 years revealed low- to very-low-certainty evidence that dietary patterns lower in red and processed meat intake result in very small or possibly small decreases in all-cause mortality, cancer mortality and incidence, cardiovascular mortality, nonfatal coronary heart disease, fatal and nonfatal myocardial infarction, and type 2 diabetes. For all-cause, cancer, and cardiovascular mortality and incidence of some types of cancer, the total sample included more than 400 000 patients; for other outcomes, total samples included 4000 to more than 300 000 patients. Limitation: Observational studies are prone to residual confounding, and these studies provide low- or very-low-certainty evidence according to the GRADE criteria. Conclusion: Low- or very-low-certainty evidence suggests that dietary patterns with less red and processed meat intake may result in very small reductions in adverse cardiometabolic and cancer outcomes. Primary Funding Source: None. (PROSPERO: CRD42017074074)